Relaxação magneto-óptica em cristais líquidos liotrópicos - Laczkowski, Ivan Marcelo (2005)
In this work we are studying the optical behavior of fluids when submitted to an external magnetic field.These isotropic fluids are doped with different concentrations of ferrofluid. More specifically, three optically isotropic fluids have been studied: water, glycerine and liquid crystal in the isotropic phase. The liquid crystal is a mixture of potassium laurate (26.89%wt) decanol (6.39%wt) and water (66.72%wt). The phase transitions of this mixture (without ferrofluid) as a function of temperature determined by optical technique are: LAM (12.0 °C) ISO (50.0 °C) where LAM is lamellar phase and ISO is isotropic phase. Each doped samples is, independently, encapsulated in a sample holder made of glass with a rectangular section shape with 9.5mm x 5.0mm (optical path) x 43.2mm (height). The cells are carefully sealed to avoid concentration gradients in the sample. The doped mixture is placed between crossed polarizers. The optical transmittance is measured using a standard technique with a He-Ne laser (λ = 632.8 nm) and a photodiode connected to an oscilloscope (Tecktronix TDS 3012). In order to promote an alignment of the ferrofluid into the sample a pulsed magnetic field is applied perpendicularly to the laser beam. The magnetic field of about 600G is a square wave with the frequency controlled by a function generator (Stanford Research system DS335). The frequency range of the magnetic field is from 0.1Hz to 2.0Hz. The experimental results are interpreted by means of Bernoulli's approach and a characteristic time is discussed when the magnetic field is turned off. Furthermore we measured viscosity of the lyotropic samples as a function of temperature by using cone-plate rheometer.